ANALISIS URAIAN TUGAS TENAGA ADMINISTRASI SEKOLAH BIDANG SARANA DAN PRASARANA DI SLTA SE- KABUPATEN PASAMAN BARAT - Sri Wulanjuni; Rusdinal Rusdinal; Anisah Anisah; Widiawati Widiawati (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aimed to analyze the job descriptions of school administrative staff in the facilities and infrastructure division at senior secondary schools throughout West Pasaman Regency. Methods: A quantitative descriptive approach was employed. The sample consisted of 46 respondents selected through simple random sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using mean scores and the Respondent Achievement Level (TCR). Results: The findings showed that the job descriptions were categorized as good, with a mean score of 4.4 and a TCR of 88.3%. The authority indicator obtained the highest TCR (88.9%), followed by responsibility (88.3%), while task clarity and work outcome standards each achieved 88.0%. Novelty: This study provides empirical evidence on the job descriptions of school administrative staff in the facilities and infrastructure division based on four dimensions: task clarity, responsibility, authority, and work outcome standards. The findings may serve as a reference for improving job description documents and strengthening school administrative management.